M7‐FLIPI is not prognostic in follicular lymphoma patients with first‐line rituximab chemo‐free therapy. (18th August 2019) - Lockmer, Sandra; Ren, Weicheng; Brodtkorb, Marianne; Østenstad, Bjørn; Wahlin, Björn E.; Pan‐Hammarström, Qiang; Kimby, Eva
Summary: The clinical course of follicular lymphoma (FL) is highly variable. Recently the m7‐FL international prognostic index (FLIPI) integrating performance status, FLIPI score and the mutational status of seven genes, was shown to stratify patients into "low‐risk" and "high‐risk" with respect to 5‐year failure‐free survival after first‐line immunochemotherapy. Our aim was to evaluate the model after rituximab without chemotherapy. The Nordic Lymphoma Group performed two randomized clinical trials on indolent lymphoma patients receiving single rituximab and rituximab with interferon‐α2a. In total, 95 FL patients had sufficient fresh‐frozen diagnostic material for sequencing. A targeted panel for the genes EZH2, ARID1A, MEF2B, EP300, FOXO1, CREBBP and CARD11 was utilized for m7‐FLIPI score calculation. With a median follow‐up of 10·6 years, 76% of patients were alive. No difference in time to treatment failure (TTF), defined as the interval between start of trial therapy and initiation of new therapy or death, nor overall survival (OS) was found between the m7‐FLIPI risk groups (log‐rank P = 0·94 and 0·99, respectively). EZH2 mutations were associated with longer TTF (log‐rank P = 0·04) and in EP300 mutations were associated with shorter TTF (log‐rank P = 0·01). We conclude that the prognostic value of the m7‐FLIPI clinicogenetic model seems dependent on therapeutic regimen.